ACCELERATION OF DIGITAL TRANSFORMATION OF THE AGRICULTURAL SECTOR OF KYRGYZSTAN BY IMPLEMENTING TECHNOLOGICAL MONITORING SOLUTIONS INTO THE DIGITAL INFRASTRUCTURE OF THE SECTOR AT THE NATIONAL AND SUPRANATIONAL LEVELS (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2026)
The article develops a theoretical and practical justification for ways to accelerate the digital transformation of the agro-industrial complex of the Kyrgyz Republic through the introduction of modern technological monitoring solutions into the digital infrastructure of this complex, taking into account the requirements of both national development and integration processes at the EAEU level. The potential and functionality of advanced and promising technological solutions for the automation of phytomonitoring, including “Field Scout”, “Photon”, sensor gas analyzers, smart hydroponics systems and the greenhouse complex “Agrobot” are revealed. A set of scientific and practical recommendations for government agencies, agribusiness and development institutions  to accelerate the digital transformation of the industry, taking into account modern challenges and strategies of the EAEU, is proposed.
Keywords: digital transformation, agriculture, Kyrgyzstan, digital infrastructure, phytomonitoring technologies, EAEU.